2011
DOI: 10.1103/physrevb.84.014426
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-one-dimensional antiferromagnetism and multiferroicity in CuCrO4

Abstract: The bulk magnetic properties of the new quasi-one-dimensional Heisenberg antiferromagnet, CuCrO4, were characterized by magnetic susceptibility, heat capacity, optical spectroscopy, EPR and dielectric capacitance measurements and density functional evaluations of the intra-and inter-chain spin exchange interactions. We found type-II multiferroicity below the Néel temperature of 8.2(5) K, arising from competing antiferromagnetic nearest-neighbor (Jnn) and next-nearest-neighbor (Jnnn) intra-chain spin exchange i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 66 publications
2
38
3
Order By: Relevance
“…The feature at high T (upturn below 100 K) may arise due to the presence of AFM couplings (short-range correlation above ordering). Similar upturn in the ε′ ( T ) has also been observed in many multiferroic and/or magneto-electric oxides due to magnetic correlations 1820 . Though, we did not observe any signature of ferroelectricity by pyoelectric measurement within the resolution limit of our instrument.
Figure 2χ( T ) measured in 0.5 T. The solid line is a fit to 1/χ data, while the dashed line represents the extrapolation.
…”
Section: Resultssupporting
confidence: 75%
“…The feature at high T (upturn below 100 K) may arise due to the presence of AFM couplings (short-range correlation above ordering). Similar upturn in the ε′ ( T ) has also been observed in many multiferroic and/or magneto-electric oxides due to magnetic correlations 1820 . Though, we did not observe any signature of ferroelectricity by pyoelectric measurement within the resolution limit of our instrument.
Figure 2χ( T ) measured in 0.5 T. The solid line is a fit to 1/χ data, while the dashed line represents the extrapolation.
…”
Section: Resultssupporting
confidence: 75%
“…In such compounds it is frequently found that the spin exchange interactions between the Cu 2+ (S=1/2) ions are such that the next-nearest-neighbor (NNN) exchange is antiferromagnetic (AFM), the nearest-neighbor (NN) exchange is ferromagnetic (FM), and the NNN spin exchange is often considerably stronger than the NN spin exchange. Due to the inherent competition of the NN and NNN spin exchange interactions, the CuX 2 ribbon chains tend to develop unusual AFM incommensurate spiral spin structures [1][2][3][4][5][6][7][8][9] and sometimes concomitantly multiferroic behavior. [10][11][12][13] These CuX 2 ribbon chains are formed by linking CuX 4 basal-square-planes of axially elongated CuX 6 (X = O, Cl, Br,...) octahedra together via their trans-edges.…”
Section: Low Dimensional Magnetic Cumentioning
confidence: 99%
“…Here, we are dealing with an insulator, in which the asymmetry arises from the influence of non-diagonal elements of the dynamic susceptibility. This effect is often observed in systems with interactions of low symmetry, geometrical frustration and sufficiently broad resonance lines (B r  B) [46][47][48][49].…”
Section: B Electron Spin Resonancementioning
confidence: 99%